Design and hardware implementation of high power factor (HPF) three-phase AC-DC converter employing current injection technique / Azmi Zulkifli - Zulkifli, Azmi (2008)
This paper proposes a high-power-factor, three- phase AC-DC converter that employs a high frequency resonant current (CISRC) topology. Resonant conversion techniques are used, and a high-frequency current injected into the three phase rectifier to achieve a high power factor. The current injection principle is explained and the results are validated by comparison with mat lab simulation and measurement from a prototype 300W and 45V input.